The Oral Cavity Potentially Serving as a Reservoir for SARS-CoV-2 but Not Necessarily Facilitating the Spread of COVID-19 in Dental Practice - Tsuchiya, Hironori (European Journal of Dentistry, 2022)
Intraoral tissues, secretions, and microenvironments may provide severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with the conditions necessary for viral cellular entry and inhabitation. The aim of the present study is to overview the oral cavity that potentially serves as a reservoir for SARS-CoV-2, and then discuss the possibility that such oral cavity facilitates the spread of coronavirus disease 2019 (COVID-19) in dental practice. Articles were retrieved from PubMed/Medline, LitCovid, ProQuest, Google Scholar, and preprint medRxiv databases. Results of the literature search indicated that SARS-CoV-2 host cell entry-relevant receptor and virus/cell membrane fusion mediators are expressed in major and minor salivary glands, tongue, taste bud, periodontal tissue, and dental pulp, which would be a target and reservoir for SARS-CoV-2. SARS-CoV-2 is present in saliva and gingival crevicular fluid of COVID-19 patients. These secretions would contaminate dental aerosol and droplet with SARS-CoV-2. SARS-CoV-2 inhabits periodontal pocket, gingival sulcus, and dental caries lesion, which could provide SARS-CoV-2 with a habitat. SARS-CoV-2 ribonucleic acid is preserved in dental calculus, which may inform of the previous infection with SARS-CoV-2. Despite involvement of the oral cavity in SARS-CoV-2 transmission and infection, to date, there have been no clusters of COVID-19 in dental practice. Dental settings are much less likely to facilitate the spread of COVID-19 compared with general medical settings, which may be explained by the situation of dentistry that the number of patients to visit dental offices/clinics was decreased during the COVID-19 pandemic, the characteristics of dentistry that dental professionals have maintained high awareness of viral infection prevention, adhered to a strict protocol for infection control, and been using personal protective equipment for a long time, the experimental results that dental devices generate only small amounts of aerosol responsible for the airborne viral transmission, irrigant from the dental unit contributes to the aerosol microbiota much rather than saliva, and the commonly used evacuation or suction system effectively reduces aerosol and droplet generation, and the possibility that human saliva exhibits the antiviral activity and the property to inhibit SARS-CoV-2 infection. It is considered that dental treatment and oral health care can be delivered safely in the COVID-19 era.
Keywords: oral cavity; SARS-CoV-2 reservoir; COVID-19 spread; dental practice; aerosol transmission